Tinjauan Literatur: Faktor Penyebab dan Dampak Perselingkuhan terhadap Pasangan dan Anak dalam Keluarga - Atiah Amalia Fanni; Dewi Natali; Dwiva Magernita Silamba (CV. ITTC INDONESIA, 2026)
Infidelity is a common phenomenon in romantic relationships, particularly during early adulthood (intimacy vs. isolation stage). It involves emotional or sexual involvement outside the primary relationship and is influenced by various factors. This study aims to examine the causes and impacts of infidelity in relationships and families. The method used is a literature review of relevant and high-quality scientific articles. The findings show that infidelity is influenced by individual, relational, and social factors. Its impacts include psychological, relational, and family aspects, such as negative emotions, loss of trust, conflict, and disturbances in children’s development. In conclusion, infidelity is a complex phenomenon with broad impacts, requiring preventive efforts through improving individual, relational, and social quality